Long Noncoding RNAs in the Regulation of Asthma: Current Research and Clinical Implications - Xueyi Zhu; Ying Wei; Ying Wei; Jingcheng Dong; Jingcheng Dong (Frontiers Media S.A., 2020)
Asthma is a chronic airway inflammatory disorder related to variable expiratory airflow limitation, leading to wheeze, shortness of breath, chest tightness, and cough. Its characteristic features include airway inflammation, airway remodeling and airway hyperresponsiveness. The pathogenesis of asthma remains extremely complicated and the detailed mechanisms are not clarified. Long noncoding RNAs (lncRNAs) have been reported to play a prominent role in asthma and function as modulators of various aspects in pathological progress of asthma. Here, we summarize recent advances of lncRNAs in asthma pathogenesis to guide future researches, clinical treatment and drug development, including their regulatory functions in the T helper (Th) 1/Th2 imbalance, Th17/T regulatory (Treg) imbalance, eosinophils dysfunction, macrophage polarization, airway smooth muscle cells proliferation, and glucocorticoid insensitivity.